Art in Early Childhood Period: Experiences and Effects - AYDOS, EMİNE HANDE (Afyon Kocatepe Üniversitesi Eğitim Fakültesi, 2025)
Art education, which contributes to a wide range of activities from supporting children's fine motor development to increasing aesthetic sensitivity, is a basic learning area that supports children's creativity and strengthens their sensory and cognitive development in the preschool period. The purpose of the research is to create a roadmap for educators engaged in art activities with children from an early age on how these activities can be conducted more effectively for the benefit of children. The study uses a qualitative design, employing phenomenology. Data was collected through in-depth interviews with two participants engaged in art activities with children, using a semi-structured interview form developed by the researcher and refined based on expert opinions. Descriptive analysis was conducted, and codes and themes were generated from the results. The findings were presented under the themes of: (1) the definition and function of art, (2) the implementation process with children, (3) its contribution to the children's development and learning, (4) evaluation process, and (5) recommendations for practitioners. According to the results obtained from the research, it is emphasized that artistic activities in early childhood should be planned according to the interests, needs, and desires of children.
Erken Çocukluk Döneminde Sanat: Deneyimler ve Etkiler
Keywords: Early Childhood Education; Art; Art Education; Phenomenology